Assessment of Digital Technology Skills and Utilization in Community Data Management: A Case Study of Khao Tum Sub-District Administrative Organization - Masamae, Nourhuda; Useng, Maroning; Masamae, Abdunfatah; Hama, Ibtisam; Worlee, Anuwat (Journal of Information Science Research and Practice, 2024)
Purpose: To assess the level of skills and application of digital technology in managing important community data under the jurisdiction of Khao Tum Sub-District Administrative Organization, Yarang District, Pattani Province. Methodology: This study uses a participatory action research with administrators, personnel from Khao Tum Sub-District Administrative Organization, and community health volunteers from the community health promotion hospital. This quantitative research analyzes data using percentage and standard deviation. Findings: The assessment of digital technology utilization for community data management under the jurisdiction of Khao Tum Sub-District municipality is categorized into three groups. First, the administrators were found to have high-level skills in applying digital technology, data management and analysis for planning and decision-making, selecting data visualization tools, and interpreting, analyzing, and communicating results, with averages of 4.20, 3.73, 4.00, and 4.07, respectively. Second, the staff were found to have high skills in all four areas, with averages of 4.20, 3.95, 3.75, and 3.60, respectively. Lastly, the community health volunteers were found to have high skills in applying digital technology, with an average of 3.95, and a strong framework for thinking about volunteering and public service, with an average of 4.20. Applications of this study: The application of these findings aims to enhance convenience, speed, and quality of public service across various dimensions with precision and efficiency. This ensures that citizens receive excellent services, reducing disparities in accessing fundamental rights they are entitled to, fostering confidence in development, and elevating service areas. This is achieved by empowering personnel with digital technology skills, enabling them to derive significant benefits and adapt to the needs of the Sub-District municipality, the Department of Local Administration, the Ministry of Interior, the Ministry of Digital Economy and Society, and the local community members who play a role in supporting the use of digital technology for community development.